Superinfection Exclusion by Incomplete Genomes of Bacteriophage T4 - Childs, J. D. (1973)
The genetic basis of superinfection exclusion by bacteriophage T4 was investigated by using incomplete genomes derived from the gene 66 mutant E920g. Incomplete genomes, which included a region of T4 between genes 42 and 44, were able to exclude superinfecting phage with an efficiency similar to that of complete genomes. Those genomes which did not include this region were unable to exclude superinfecting phage. A mutant with reduced ability to exclude super-infecting phage was isolated after mutagenesis with hydroxylamine. The mutation maps midway between amN122 in gene 42 and amB22 in gene 43. The efficiency of exclusion of superinfecting phage (as measured by the percentage of superinfected cells which failed to release any phage carrying selected markers of the superinfecting phage) by this mutant was 50 to 60%, whereas for wild type it was 85 to 95%. Uptake of (3)H-leucine by cells infected with the mutant was inhibited by superinfection with ghosts and it has therefore been designated imm1, for lack of immunity to superinfecting phage and ghosts. The formation of infective centers by cells infected with imm1 or another imm(−) mutant (imm2) was not inhibited by superinfection with ghosts.